A Model for the Rescue and Public Relief Disaster with Buddhist Integration - siriratpiriya, rachaphol; Phra Panyavajrapandit; พระมหาอดิเดช สติวโร (Mahachula Academic Journal, 2025)
The research aims to: 1) study the operations of rescue and disaster relief organizations, 2) integrate Buddhadhamma and the role of monks in public welfare promoted rescue and public relief disaster, and 3) propose a model for the rescue and public relief disaster with Buddhist integration. This qualitative field research was conducted by collecting data from the Tipitaka, Visuddhimuk included textbooks, academic and research articles, besides in-depth interviews in Nan province by in-depth interviews with structured interview. The key informant groups are ecclesiastical administrative officer and representative from the public and private organizations involved in rescue and public relief disaster. All of data were collected, analysis and synthesis to elaborate by descriptive technique further to develop a model for the rescue and public relief disaster with Buddhist integration, then tests the said model with expert group discussion techniques for its feasibility and practicality. The results showed that: (1) The operations of rescue and disaster relief organizations are involved in birth, aging, sickness, and death. They have to work against time to save lives and carry out resuscitation under the Emergency Medical Act B.E. 2551 (2008) and public relief disaster under the Disaster Prevention and Mitigation Act B.E. 2550 (2007). The operation unit must be approved as medical unit. Emergency Operations Unit Personnel must be trained in accordance with emergency medical standards. (2) The intention or karma including bodily, verbal, and mental action is the source and the core of all behaviors. The Buddhadhamma that are linked to intentions or karma as mental concomitants, such as Hiri Ottapp, Bhavana 4, Brahma Vihara 4, Itthipat 4, Gharavasa Dhamma 4, Sangkahavattu 4, Ariyasapa 7, and Yonisomanasikan together with proper intention and earnestness integrated for work before, during, and after a public disaster enhanced practitioners’ awareness and moral responsibility. The Buddhadhamma intention 3, namely preliminary intention, releasing intention, and subsequent intention, including the role of a public welfare monk as aid, support, development, and integration plus the role of Phrakilanupatakata in well being are similar and can be integrated with holistic principles of disaster risk management for sustainable safety, in short the 2P2R principle consisted of Preparedness, Prevention and Mitigation, Response, and Recovery. (3). A model for the rescue and public relief disaster with Buddhist integration is a schematic model of relationship, collaboration, and the holistic disaster risk management worked under guideline 2P2R principle and the Buddhist principle of intention or karma which is both the source and core of all behavior in physical, verbal, and mental expressions, including moral dread (Hiri Ottapp) and mindfulness as the axis of behavior by the preliminary intention, releasing intention and subsequence intention, as well as the role of the monks of public welfare and Phrakilanupatakata who participates in both material and mental assistance in relieving, supporting, developing, and integrating both normal and crisis situations. All of the said factors have been integrated to intention of the one who involved in practical work before, during and after the occurrence of a rescue and public disaster.